Penafsiran Hukum Atas Kewenangan Notaris Dalam Menjalankan Jabatan Diluar Tempat Kedudukannya Berdasarkan UUJN Dan KEN - Adi Tatar, Ketut Wiranata; Sarna, Kadek (Acta Comitas, 2025)
This study analyzes the interpretation of Certain Reasons in Article 3 Paragraph 15 of the Notary Code of Ethics and “Consecutiveas’’ a limitation on a notary's authority outside their domicile. It also evaluates Consecutive from the perspective of justice and legal equality to strengthen the legal framework supporting notary professionalism. This study uses a normative legal research method, using the Statute Approach and the Conceptual Approach. The results of the study show that the Interpretation of the phrase certain reasons in Article 3 Paragraph” 15 of the Code of Ethics of the Indonesian Notary Association refers to the notary's obligation to carry out duties in his/her office, with exceptions only for legally valid conditions, not personal reasons. Carrying out duties outside the office, such as in making a release deed, is justified if it is in accordance with legal provisions. Meanwhile, the interpretation of the consecutive phrases in Article 19 paragraph (3) of the UUJN is important to ensure the limits of the notary's authority outside his/her jurisdiction. Without a clear interpretation, uncertainty and abuse of authority can arise. Therefore, this norm needs to be reconstructed with clear limits regarding the time and number of deeds outside the office, accompanied by clear sanctions so that the notary's authority is carried out professionally and in accordance with the principles of justice.